Effect of brine on the kinetics of Carbon dioxide hydrate formation and dissociation in porous media - Rehman, A.N. (Elsevier Ltd, 2020)
In this paper, the kinetics of CO2hydrate formation and dissociation was studied experimentally in porous media (quartz sand) to evaluate the effect of brine on CO2hydrate storage capacity. The experiments were performed using the constant cooling and heating method in a high pressure hydrate reactor at an exprimental formation pressure and temperature of 4 MPa and 274.15 K and dissociation temperature at 277.15 K, respectively. The brine system (3.3 wt NaCl) was used at 100 saturation for 6.5 cm bed height. The results showed that the disruptive effect of the salt ions in brine on the CO2hydrate structure in the porous media prolongs the hydrate nucleation time and reduces the CO2storage capacity by 30 and 32, respectively. In addition, the presence of brine affects the hydrate dissociation stability by increasing the rate of hydrate dissociation from 0.0127 mol/h to 0.0656 mol/h. The time taken to achieve 90 CO2release was reduced by 29 in the presence of brine. The results in this work are useful for hydrate-based CO2storage technology in porous media. Â© 2020 Elsevier Ltd. All rights reserved.